Working: Images of Canadian Labour, 1900-2000 = Travailler : images de la vie ouvrière au Canada, 1900-2000 - Barna, Laszlo (Key Porter Books, 1999)
The companion book to The Labour Millenium Project, a four-part documentary film series and CD-ROM --Page 4 of cover. Text in English and French.
Keywords: 1900-1999; Canada; Grèves et lock-out Canada Histoire 20e siècle Ouvrages illustrés; History; Labor movement; Labor movement Canada History 20th century Pictorial works; Labor unions; Labor unions Canada History Pictorial works; Mouvement ouvrier Canada Histoire 20e siècle Ouvrages illustrés; Pictorial works; Strikes and lockouts; Strikes and lockouts Canada History 20th century Pictorial works; Syndicats Canada Histoire Ouvrages illustrés; Travailleurs Canada Histoire 20e siècle Ouvrages illustrés; Working class; Working class Canada History 20th century Pictorial works